Preparation method of 5000 series marble grain aluminum alloy for anodic oxidation

Through the preparation method of the 5000 series marble pattern anodizing aluminum alloy, the problem of solid color and limited differences in existing anodized products is solved, and the effect of marble pattern after anodizing is achieved, and the appearance level of the product is improved.

CN119685642APending Publication Date: 2025-03-25CHINALCO RUIMIN CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411910153.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing anodized aluminum plate products are all solid colors, and the product differences are mainly due to the difference in the color uniformity of the anode, which has reached a bottleneck. The market urgently needs to develop a new anodizing effect to widen the direction of anode oxidation of aluminum alloys.

Method used

The preparation method of the 5000-type aluminum alloy for anodizing marble pattern was used to prepare an aluminum alloy sheet in the Al-Mg-type H12 state for anodizing marble patterns by melting, casting, hot rolling, continuous annealing and cold rolling of aluminum ingots, aluminum intermediate alloy ingots and electrolytic aluminum water raw materials.

Benefits of technology

It realizes the enlargement of the grain size through special processing methods, so that the anodized appearance will appear marble after being anodized, with unique appearance advantages and can effectively improve the product grade.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a preparation method of 5000 series marble grain aluminum alloy for anodic oxidation, which comprises the following steps of: optimizing chemical components, a hot rolling process, an annealing mode and the like, and adopting a small-working-rate cold rolling mode to reduce the influence of the rolling process on the grain shape; and the Al-Mg series H12 state aluminum alloy sheet for anodic oxidation with marbling is prepared, wherein the average grain diameter of the Al-Mg series H12 state aluminum alloy sheet for anodic oxidation is 0.5-1.5 mm, and the grain size is uniform. The novel anodic oxidation effect is achieved, the appearance similar to marble-shaped patterns can be obtained after the product is machined through a conventional anodic oxidation procedure, the product has the unique appearance advantage compared with a conventional anodic oxidation product, and the product grade can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nonferrous metals, and in particular relates to a method for preparing a 5000 series marble-grained anodized aluminum alloy. Background Art

[0002] At present, the mainstream anodized aluminum plates are mainly pure colors, and the product differences are mainly in the difference in the uniformity of the anode color, but the development of anode uniformity has reached a bottleneck. Now the market is in urgent need of developing a new anodizing effect to expand the direction of aluminum alloy anodizing. In order to obtain a more unique product appearance, the present invention proposes a patterned anodized aluminum substrate. After the product is processed by the conventional anodizing process, it can obtain an appearance similar to a marble pattern. Compared with conventional anodized products, it has a unique appearance advantage and can effectively improve the product grade. Summary of the invention

[0003] The purpose of the present invention is to provide a method for preparing a 5000 series marble-patterned anodized aluminum alloy in view of the shortcomings of the prior art.

[0004] To achieve the above object, the present invention adopts the following technical solutions: A 5000 series marble-patterned aluminum alloy for anodizing is an Al-Mg series H12 aluminum alloy sheet for anodizing with a marble pattern, which is made from aluminum ingots, aluminum master alloy ingots, and electrolytic aluminum liquid raw materials through smelting, casting, hot rolling, continuous annealing, and cold rolling.

[0005] The preparation method of the 5000 series marble-patterned anodized aluminum alloy comprises the following steps: 1) According to the alloy composition ratio, the aluminum ingot, the master alloy ingot and the electrolytic aluminum liquid raw materials are melted, refined, deslagging and degassing, and then semi-continuously cast into 400-460mm thick aluminum alloy flat ingots; 2) The obtained aluminum alloy flat ingot is subjected to homogenization heat treatment after milling, and hot rolled using a 1+3 hot rolling mill after being taken out of the furnace; 3) annealing the hot rolled coil obtained in step 2) in a continuous annealing furnace; 4) The coil obtained in step 3) is cold-rolled into a finished product with a thickness of 2.0-5.0 mm, so as to obtain an Al-Mg series H12 aluminum alloy sheet for anodizing with a marble pattern.

[0006] Furthermore, based on the sum of the mass percentages being 100%, the mass percentages of the chemical components in the aluminum alloy are: Si 0.06-0.14%, Fe 0.04~0.10%, Cu≤0.05%, Mn≤0.05%, Mg 2.2~2.35%, Cr 0.15-0.18%, Ti 0.025~0.035%, and the remainder being aluminum and unavoidable impurities.

[0007] Furthermore, in step 1), the casting temperature needs to be controlled at 690-715°C.

[0008] Furthermore, in step 2), when hot rolling is performed, the hot rough rolling passes are 11 passes, and the processing rate of the last two passes is controlled at 38%-50%.

[0009] Furthermore, in step 2), when hot rolling is performed, the hot finishing rolling convexity is set to 0.3, and the hot rolled coil is rolled to a thickness of 2.5-3.0 mm, and the final rolling temperature is 250-270°C.

[0010] Furthermore, the annealing temperature in step 3) is 560-600°C, the heating rate is ≥10°C / s, the holding time is controlled at 200-300s, and the temperature difference is controlled at 3°C; the cooling method is water cooling, and the water pressure is controlled at 3-5bar.

[0011] Furthermore, in step 4), the cold rolling processing rate is controlled at 8%-10%.

[0012] Furthermore, the average grain diameter of the obtained finished product is 0.5-1.5 mm.

[0013] The technical features of the present invention are: (1) The chemical composition formula of the present invention adopts lower Si, Fe, Cu and Mn element contents, which avoids the premature growth of individual grains in the subsequent recrystallization process and affects the uniformity of the finished grains.

[0014] (2) The present invention controls the thickness of the ingot to ensure the uniformity of the solidification of the entire liquid cavity during the casting process, thereby improving the uniformity of the ingot grains. However, too low a casting temperature can easily lead to the generation of bright crystals.

[0015] (3) In the hot rolling process of the present invention, the number of hot rough rolling passes and the processing rate of the last two passes are controlled to break the grains as much as possible through a large reduction, thereby further homogenizing the grain size. The final rolling temperature is controlled at 250-270°C to prevent the hot rolled coil from being completely recrystallized, providing energy storage for subsequent continuous annealing to increase the grain size.

[0016] (4) The high heating rate during the annealing process of the present invention is to ensure the uniformity of the grain size as much as possible; the annealing temperature of 560-600°C and the holding time of 200-300s can ensure that the grains grow to 0.5-1.5mm, so that the material presents a marble appearance after anodization.

[0017] (5) In order to meet the mechanical properties of aluminum alloy products, cold rolling hardening is required. At the same time, in order to avoid excessive cold rolling processing rate causing grain elongation, the cold rolling processing rate needs to be controlled at 8%-10%.

[0018] The significant advantages of the present invention are: The present invention proposes a patterned anodized aluminum substrate, which enlarges the size of the grains to a level visible to the naked eye through a special processing method, and under the premise of ensuring a high degree of size uniformity, affects the formation process of the anodized film at the corresponding position through the different orientations of different grains after anodization, thereby obtaining a special appearance similar to a marble pattern. Compared with conventional anodized products, it has a unique appearance advantage and can effectively improve the product grade. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a surface image of the aluminum alloy sheet prepared in the example after being anodized.

[0020] Figure 2 This is the surface image of the aluminum alloy sheet prepared in Comparative Example 1 after anode treatment.

[0021] Figure 3 This is the surface image of the aluminum alloy sheet prepared in Comparative Example 2 after being anodized.

[0022] Figure 4 This is the surface image of the aluminum alloy sheet prepared in Comparative Example 3 after anode treatment. DETAILED DESCRIPTION

[0023] A 5000 series marble-patterned anodized aluminum alloy, the preparation method of which comprises the following steps: 1) According to the alloy composition ratio, aluminum ingots, master alloy ingots and electrolytic aluminum liquid raw materials are melted, refined, deslagging and degassing, and then semi-continuously cast at 690-715° C. into aluminum alloy flat ingots with a thickness of 400-460 mm; based on the sum of mass percentages being 100%, the mass percentages of the chemical components in the aluminum alloy are: Si 0.06-0.14%, Fe 0.04-0.10%, Cu≤0.05%, Mn≤0.05%, Mg 2.2-2.35%, Cr0.15-0.18%, Ti 0.025-0.035%, and the balance is aluminum and unavoidable impurities; 2) After milling, the obtained aluminum alloy flat ingot is kept at 520℃ for 4h to achieve homogenization annealing, and then hot rolled using a 1+3 hot rolling mill after being taken out of the furnace; the hot rough rolling passes are 11 passes, and the processing rate of the last 2 passes is controlled at 38%-50%; the hot finishing rolling crown is set to 0.3, and the hot rolled coil is rolled into a thickness of 2.5-3.0mm, and the final rolling temperature is 250-270℃; 3) The hot rolled coil obtained in step 2) is annealed in a continuous annealing furnace; the annealing temperature is 560-600°C, the heating rate is ≥10°C / s, the holding time is controlled at 200-300s, and the temperature difference is controlled at 3°C; the cooling method is water cooling, and the water pressure is controlled at 3-5bar; 4) The coil obtained in step 3) is cold rolled, and the cold rolling processing rate is controlled at 8%-10%, and rolled into a finished product with a thickness of 2.0-5.0 mm to obtain an Al-Mg series H12 state aluminum alloy sheet for anodizing with a marble pattern, and the average grain diameter thereof is 0.5-1.5 mm.

[0024] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.

[0025] Experimental example 1) According to the alloy composition ratio, aluminum ingots, master alloy ingots and electrolytic aluminum liquid raw materials are melted, refined, deslagging and degassing, and then semi-continuously cast at 700° C. into aluminum alloy flat ingots with a thickness of 400-460 mm; based on the sum of mass percentages being 100%, the mass percentages of the chemical components in the aluminum alloy are: Si 0.08%, Fe 0.07%, Cu 0.0003%, Mn 0.0001%, Mg2.42%, Cr 0.16%, Ti 0.029%, and the balance is aluminum and unavoidable impurities; 2) After milling, the obtained aluminum alloy flat ingot was kept at 520℃ for 4h to achieve homogenization annealing, and then hot rolled using a 1+3 hot rolling mill after being taken out of the furnace; hot rough rolling was performed for 11 passes, and the processing rate of the last 2 passes was controlled at 42%; the hot finishing rolling crown was set to 0.3, and the hot rolled coil was rolled into a 2.5mm thick hot rolled coil, and the final rolling temperature was 260℃; 3) The hot rolled coil obtained in step 2) is annealed in a continuous annealing furnace, the annealing temperature is 580°C, the heating rate is ≥10°C / s, the holding time is controlled at 250s, the temperature difference is controlled at 3°C; the cooling method is water cooling, and the water pressure is controlled at 3bar; 4) The coil obtained in step 3) is cold rolled, and the cold rolling processing rate is controlled at 8%, and rolled into a finished product with a thickness of 2.0 mm.

[0026] The finished product has a grain size of 0.5-1.0 mm, and the grain size is uniform with no significant difference. The measured tensile strength is 192 MPa, the yield strength is 160 MPa; the elongation is 8.9%; the roughness is 0.3 μm, which is not significantly different from the roughness of conventional anodized materials (0.2-0.4 μm). After the sample is anodized, a clear and uniform pattern can be seen on the surface (such as Figure 1 ): Comparative Example 1 1) According to the alloy composition ratio, aluminum ingots, master alloy ingots and electrolytic aluminum liquid raw materials are melted, refined, deslagging and degassing, and then semi-continuously cast at 700° C. into aluminum alloy flat ingots with a thickness of 400-460 mm; based on the sum of mass percentages being 100%, the mass percentages of the chemical components in the aluminum alloy are: Si 0.08%, Fe 0.07%, Cu 0.0003%, Mn 0.0001%, Mg2.42%, Cr 0.16%, Ti 0.029%, and the balance is aluminum and unavoidable impurities; 2) After milling, the obtained aluminum alloy flat ingot was kept at 520℃ for 4h to achieve homogenization annealing, and then hot rolled using a 1+3 hot rolling mill after being taken out of the furnace; hot rough rolling was performed for 11 passes, and the processing rate of the last 2 passes was controlled at 42%; the hot finishing rolling crown was set to 0.3, and the hot rolled coil was rolled into a 2.5mm thick hot rolled coil, and the final rolling temperature was 260℃; 3) The hot rolled coil obtained in step 2) is annealed in a common box, the annealing temperature is 500°C, the heating rate is about 1°C / min, the holding time is controlled at 1h, the temperature difference is controlled at 5°C; the cooling method is water cooling, and the water pressure is controlled at 3bar; 4) The coil obtained in step 3) is cold rolled, and the cold rolling processing rate is controlled at 8%, and rolled into a finished product with a thickness of 2.0 mm.

[0027] The finished product grain size is 0.05-4mm, with large grain size differences, and there are large grains with a grain size of 2-4mm. The measured tensile strength is 172MPa, the yield strength is 132MPa; the elongation is 9.1%; the roughness is 0.28μm. After the sample is anoded, clear patterns can be seen on the surface, but due to the presence of large grains, the surface pattern is uneven (such as Figure 2 ).

[0028] Comparative Example 2 1) According to the alloy composition ratio, aluminum ingots, master alloy ingots and electrolytic aluminum liquid raw materials are melted, refined, deslagging and degassing, and then semi-continuously cast at 700° C. into aluminum alloy flat ingots with a thickness of 400-460 mm; based on the sum of mass percentages being 100%, the mass percentages of the chemical components in the aluminum alloy are: Si 0.08%, Fe 0.07%, Cu 0.0003%, Mn 0.0001%, Mg2.42%, Cr 0.16%, Ti 0.029%, and the balance is aluminum and unavoidable impurities; 2) After milling, the obtained aluminum alloy flat ingot is kept at 520℃ for 4h to achieve homogenization annealing, and then hot rolled using a 1+3 hot rolling mill after being taken out of the furnace; hot rough rolling is performed for 11 passes, and the processing rate of the last 2 passes is controlled at 42%; the hot finishing rolling crown is set to 0.3, and the hot rolled coil is rolled into a 5.1mm thick hot rolled coil, and the final rolling temperature is 320℃; 3) The hot rolled coil obtained in step 2) is cold rolled to 2.7 mm, and then annealed in a continuous annealing furnace, with an annealing temperature of 580°C, a heating rate of ≥10°C / s, a holding time of 250s, and a temperature difference controlled at 3°C; the cooling method is water cooling, and the water pressure is controlled at 3 bar; 4) The coil obtained in step 3) is cold rolled, and the cold rolling processing rate is controlled at 8%, and rolled into a finished product with a thickness of 2.0 mm.

[0029] The finished product grain size is 0.1-0.3mm, the grain size is uniform, and there is no obvious difference. The measured tensile strength is 200MPa, the yield strength is 168MPa; the elongation is 9.3%; the roughness is 0.34μm. The surface pattern size of the sample after anodization is too small to get a good appearance experience under naked eye observation (such as Figure 3 ).

[0030] Comparative Example 3 1) According to the alloy composition ratio, aluminum ingots, master alloy ingots and electrolytic aluminum liquid raw materials are melted, refined, deslagging and degassing, and then semi-continuously cast at 700° C. into aluminum alloy flat ingots with a thickness of 400-460 mm; based on the sum of mass percentages being 100%, the mass percentages of the chemical components in the aluminum alloy are: Si 0.14%, Fe 0.21%, Cu 0.004%, Mn 0.003%, Mg2.47%, Cr 0.18%, Ti 0.021%, and the balance is aluminum and unavoidable impurities; 2) After milling, the obtained aluminum alloy flat ingot was kept at 520℃ for 4h to achieve homogenization annealing, and then hot rolled using a 1+3 hot rolling mill after being taken out of the furnace; hot rough rolling was performed for 11 passes, and the processing rate of the last 2 passes was controlled at 42%; the hot finishing rolling crown was set to 0.3, and the hot rolled coil was rolled into a 2.5mm thick hot rolled coil, and the final rolling temperature was 260℃; 3) The hot rolled coil obtained in step 2) is annealed in a continuous annealing furnace, the annealing temperature is 580°C, the heating rate is ≥10°C / s, the holding time is controlled at 250s, the temperature difference is controlled at 3°C; the cooling method is water cooling, and the water pressure is controlled at 3bar; 4) The coil obtained in step 3) is cold rolled, and the cold rolling processing rate is controlled at 8%, and rolled into a finished product with a thickness of 2.0 mm.

[0031] The finished product grain size is 0.05-3mm, with large grain size differences, and there are large grains with a grain size of 2-3mm. The measured tensile strength is 165MPa, the yield strength is 122MPa; the elongation is 8.7%; the roughness is 0.35μm. After the sample is anoded, clear patterns can be seen on the surface, but due to the presence of large grains, the surface pattern is uneven (such as Figure 4 ).

[0032] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.

Claims

1. A method for preparing a 5000 series marble-patterned anodized aluminum alloy, characterized in that: An Al-Mg aluminum alloy sheet in H12 state for anodizing with marble pattern is prepared by using aluminum ingot, aluminum intermediate alloy ingot and electrolytic aluminum liquid as raw materials through smelting, casting, hot rolling, continuous annealing and cold rolling.

2. The preparation method according to claim 1, characterized in that: The following steps are involved: 1) According to the alloy composition ratio, the aluminum ingot, the master alloy ingot and the electrolytic aluminum liquid raw materials are melted, refined, deslagging and degassing, and then semi-continuously cast into 400-460mm thick aluminum alloy flat ingots; 2) The obtained aluminum alloy flat ingot is subjected to homogenization heat treatment after surface milling, and hot rolled using a 1+3 hot rolling mill after being taken out of the furnace; 3) annealing the hot rolled coil obtained in step 2) in a continuous annealing furnace; 4) The coil obtained in step 3) is cold-rolled into a finished product with a thickness of 2.0-5.0 mm, so as to obtain an Al-Mg series H12 aluminum alloy sheet for anodizing with a marble pattern.

3. The preparation method according to claim 2, characterized in that: When the sum of the mass percentages is 100%, the mass percentages of the chemical components in the aluminum alloy are: Si 0.06-0.14%, Fe 0.04~0.10%, Cu≤0.05%, Mn≤0.05%, Mg 2.2~2.35%, Cr 0.15-0.18%, Ti 0.025~0.035%, and the remainder is aluminum and unavoidable impurities.

4. The preparation method according to claim 2, characterized in that: Step 2) During hot rolling, the hot rough rolling passes are 11 passes, and the processing rate of the last two passes is controlled at 38%-50%.

5. The preparation method according to claim 2, characterized in that: Step 2) During hot rolling, the hot finishing rolling convexity is set to 0.3, and the hot rolled coil is rolled to a thickness of 2.5-3.0 mm, and the final rolling temperature is 250-270°C.

6. The preparation method according to claim 2, characterized in that: The annealing temperature in step 3) is 560-600°C, the heating rate is ≥10°C / s, the holding time is controlled at 200-300s, and the temperature difference is controlled at 3°C; the cooling method is water cooling, and the water pressure is controlled at 3-5bar.

7. The preparation method according to claim 2, characterized in that: In step 4), the cold rolling processing rate is controlled at 8%-10%.

8. The preparation method according to claim 2, characterized in that: The average grain diameter of the finished product is 0.5-1.5 mm.

9. A 5000 series marble-patterned anodized aluminum alloy prepared by the method of claim 1.